Nurturing the Child's Nature: Revisiting Child Moral Education in the Thought of Ibn Jazar on the book Siyasatu shibyan wa tadbiruhum - Al-Fatih, Muhammad Hanif (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study revisits child moral education through the lens of Ibn Jazar’s book Siyasatu shibyan wa tadbiruhum, exploring its relevance to contemporary Islamic education. The study aims to bridge the classical nature versus nurture debate in moral education, focusing on how Ibn Jazar integrates physical health with moral development. His holistic approach emphasizes that a child’s physical well-being is crucial for the effective internalization of moral values, arguing that healthy children are better prepared for moral instruction. Design/methods/approach – The research methodology employed is qualitative content analysis, with an emphasis on latent analysis to uncover hidden meanings in the text. The analysis reveals that Ibn Jazar’s work provides a comprehensive framework for addressing both physical and moral development, which is essential for shaping children’s character from an early age. Findings – The findings suggest that his emphasis on health as a foundation for morality is not only relevant for historical discourse but also offers practical solutions to current challenges in Islamic education, particularly in navigating the effects of globalization on moral development. Research implications/limitations – The study acknowledges the limitation of possible interpretative bias and recommends further research to explore how Ibn Jazar's ideas could be adapted into modern curricula. Practical implications – Practically, Ibn Jazar's approach offers guidance in the development of Islamic education curricula that focus on a balance between moral and physical instruction, while emphasizing the importance of a supportive environment for children's development. Originality/value – This research contributes to the field by highlighting a largely overlooked figure in Islamic moral education and suggesting how his interdisciplinary approach can inform the development of contemporary educational systems. Paper type Research paper